The Role of Indigenous Mycorrhizae of Corn Plants in Various Soil Types in Gunung Kidul, Indonesia - Diannastiti, Fani Aulia; Utami, Sri Nuryani Hidayah; Widada, Jaka (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2022)
Indigenous Vesicular-Arbuscular Mycorrhizae (VAM) are natural mycorrhizae from specific areas that have good environmental adaptability. This study, conducted from January to November 2020 at the Faculty of Agriculture, Universitas Gadjah Mada, aimed to isolate the vesicular-arbuscular mycorrhizal fungus so that it can be used as information on the type and role of VAM on Gunung Kidul soil. The research was arranged in a Completely Randomized Design (CRD) with three factors. The first factor was soil type from Gunung Kidul Regency (Inceptisol, Mollisol, and Alfisol), the second factor was sterilization (sterilized soil and unsterilized soil), and the third factor was corn variety (local and hybrid). Analysis of soil and plant growth was performed by using Analysis of Variance (ANOVA) and Tukey's Honestly Significant Difference (Tukey's HSD) Test. Genetic detection of root infecting VAM was performed by using Terminal Restriction Fragment Length Polymorphism (T-RFLP) method with FAM AML1-AML2 labeled primers. The VAM detected in the roots of hybrid variety included Acaulospora sp., Gigaspora sp., and Septoglomus sp., and those in the roots of local variety were Acaulospora sp., Gigaspora sp., and Funelisformis sp. The results showed that the role of VAM could be seen through unsterilized soil so that there was no VAM elimination in the soil. Unsterilized soil showed the best results of root infection, leaf fresh and dry weight, leaf phosphor (P) content, and leaf P uptake. Meanwhile, Alfisol showed the best result of root infection, fresh weight, dry weight, leaf P content, and leaf P uptake. The treatment of plant varieties showed that the varieties did not significantly affect the root infection, fresh weight, dry weight, leaf P content, and leaf P uptake.